A method for preparing high-purity and high-crystallinity double-walled carbon nanotubes in large quantities

By introducing nitrogen gas into the floating catalyst chemical vapor deposition method to promote the nucleation of the catalyst and optimize the carbon source supply, the problems of low enrichment and low yield in the preparation of double-wall carbon nanotubes are solved, and high purity and high crystallinity are achieved. Macro-preparation and high-capacity production of wall carbon nanotubes.

CN116375003BActive Publication Date: 2025-02-14INST OF METAL RESEARCH - CHINESE ACAD OF SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310228918.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-10
Publication Date
2025-02-14
Estimated Expiration
2043-03-10

AI Technical Summary

Technical Problem

The existing floating catalyst chemical vapor deposition method used to prepare double-wall carbon nanotubes has problems such as low enrichment, many impurities in the product, poor crystallinity, high catalyst content and low yield, resulting in the product being unable to fully utilize the double-wall carbon nanotubes. intrinsic performance advantages.

Method used

By introducing an appropriate amount of nitrogen into the reaction system, a catalyst with uniform particle size is prepared, and the ratio of nucleation of double-wall carbon nanotubes is increased. At the same time, the carbon source supply rate in the tube reactor is optimized to improve the growth rate and yield of double-wall carbon nanotubes.

Benefits of technology

The macro-preparation of high-purity and high-crystalline double-wall carbon nanotubes has been achieved. The quantity content of double-wall carbon nanotubes in the product is higher than 90%, the catalyst residue is less than 6wt%, and the process has high productivity and can be continuously Efficient preparation under chemical production conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116375003B_ABST
    Figure CN116375003B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of carbon nanotube structure control preparation, specifically a method for preparing double-walled carbon nanotubes in large quantities with high purity and high crystallinity. The floating catalyst chemical vapor deposition method is adopted, and the catalyst nucleation is promoted by introducing an appropriate amount of nitrogen into the reaction system, the catalyst quantity and size are adjusted, and a catalyst with uniform particle size is prepared. The nucleation ratio of double-walled carbon nanotubes can be increased by combining the growth kinetics process control, and the growth rate and yield of double-walled carbon nanotubes can be increased by optimizing the carbon source supply rate in the tubular reactor. The carbon nanotubes have high crystallinity, an oxidation decomposition temperature range of 700 to 920°C, a catalyst content of less than 6wt%, and a double-walled carbon nanotube macrobody of 500 cubic centimeters per hour is produced in a 6.5 cm diameter tubular reactor. The present invention realizes the large-scale preparation of double-walled carbon nanotubes with high purity and high crystallinity, which is of great significance to promoting the practical application of double-walled carbon nanotubes in the fields of structural functional fibers, composite materials, multifunctional braids, electronic devices, etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of structure-controlled preparation of carbon nanotubes, in particular to a method for preparing large quantities of high-purity and high-crystallization double-walled carbon nanotubes. Background Art

[0002] Double-walled carbon nanotubes are one-dimensional seamless hollow tubes formed by coaxially curling double-layer graphene. As an intermediate structure between single-walled carbon nanotubes and multi-walled carbon nanotubes, double-walled carbon nanotubes have the intrinsic performance advantages of both. Double-walled carbon nanotubes have better thermal stability and higher tensile strength than single-walled carbon nanotubes, smaller diameter, larger aspect ratio, better flexibility, and excellent mechanical, electrical, and thermal properties. The outer tube wall can be modified and modified, while the inner tube wall maintains the unique properties of carbon tube intrinsic electron and phonon transport. Therefore, double-walled carbon nanotubes have many performance advantages that single-walled and multi-walled carbon nanotubes do not have.

[0003] The development of large-scale preparation technology of double-walled carbon nanotubes is a prerequisite for their practical application. The preparation methods of double-walled carbon nanotubes include fullerene filling thermal polymerization in single-walled carbon nanotubes (Reference 1: Bandow S, Takizawa M, Hirahara K, et al.. Chemical Physics Letters, 2001, 337 (1-3): 48-54), hydrogen arc method (Reference 2: Hutchison J L, Kiselev NA, Krinichnaya EP, et al.. Carbon, 2001, 39 (5): 761-770), chemical vapor deposition method (Reference 3: Huang JQ, Zhang Q, Zhao MQ, et al.. Nano Res, 2009, 2: 872–881,), etc. Among them, the fullerene filling thermal polymerization method in single-walled carbon nanotubes has very strict requirements on the diameter of single-walled carbon nanotubes, and it is extremely difficult to uniformly fill fullerenes in single-walled carbon nanotubes. Therefore, this method cannot produce double-walled carbon nanotubes in large quantities; the double-walled carbon nanotubes prepared by the hydrogen arc method have a wide diameter distribution, and the product contains a large amount of highly crystalline graphite flakes, the product is difficult to purify, the yield is low and it is not easy to produce continuously; the chemical vapor deposition method is currently the mainstream method for preparing double-walled carbon nanotubes because of its simple equipment, convenient process control, the product does not contain difficult-to-remove graphitized impurities, and is expected to achieve high production capacity.

[0004] The chemical vapor deposition method for preparing double-walled carbon nanotubes mainly includes the support method (reference 4: Ning GQ, Liu Y, Wei F, et al.. J Phys Chem C, 2007, 111: 1969–1975,) and the floating catalyst chemical vapor deposition method (reference 5: Wu ZP, Wang J N. Physica E, 2009, 77-81). The support method is to support the catalyst on a micro-nanoscale carrier to grow double-walled carbon nanotubes, so the prepared product carbon nanotubes are mixed with the carrier; the subsequent removal of the carrier will destroy the intrinsic structure of the double-walled carbon nanotubes, resulting in many defects and poor quality of the product. The catalyst in the floating catalyst method does not require a carrier, but floats in the carrier gas to grow double-walled carbon nanotubes; therefore, the product does not contain impurities such as carriers, and the raw materials in the floating catalyst method are continuously supplied from one end of the tubular reactor, and the product is continuously produced from the other end. It is a continuous preparation method for double-walled carbon nanotubes.

[0005] At present, the problems of preparing double-walled carbon nanotubes by floating catalyst chemical vapor deposition are: the enrichment of double-walled carbon nanotubes is not high, and the product is usually a mixture of double-walled carbon nanotubes and carbon nanotubes with other wall numbers; double-walled carbon nanotubes have many defects, poor crystallinity, many impurities, high catalyst content, and low yield. Such products cannot give full play to the intrinsic performance advantages of double-walled carbon nanotubes in subsequent use, and the low production capacity also greatly limits the development of subsequent research work and large-scale application. Therefore, the development of a large-scale preparation method for high-purity and high-crystalline double-walled carbon nanotubes has important academic significance and practical value. Summary of the invention

[0006] The purpose of the present invention is to provide a large-scale preparation method of high-purity and high-crystallization double-walled carbon nanotubes, which adopts a floating catalyst chemical vapor deposition method, promotes catalyst nucleation by introducing an appropriate amount of nitrogen into the reaction system, prepares a catalyst with uniform particle size, combines growth kinetics process control to increase the nucleation ratio of double-walled carbon nanotubes, and optimizes the carbon source supply in a tubular reactor to increase the growth rate and yield of double-walled carbon nanotubes.

[0007] The technical solution of the present invention is:

[0008] A method for preparing high-purity, high-crystallization double-walled carbon nanotubes in large quantities adopts a floating catalyst chemical vapor deposition method, hydrocarbons toluene, methane, and ethylene are used as carbon sources, ferrocene is used as a catalyst precursor, and thiophene is used as a promoter precursor. The specific process flow is as follows: ferrocene and thiophene are dissolved in toluene to form a mixed solution, the mixed solution is uniformly injected into a tubular reactor, and nitrogen, hydrogen, methane, and ethylene are introduced at the same time to grow double-walled carbon nanotubes.

[0009] The method for preparing high-purity, high-crystallinity double-walled carbon nanotubes in large quantities comprises the following steps: the mass ratio of ferrocene, thiophene and toluene in a mixed solution is (10-25):(0.5-3):100; the solution injection speed is 10-50 μl / min; the total flow rate of nitrogen and hydrogen is 5-10 liters / min; the nitrogen / hydrogen flow ratio is 1.5-4; the methane supply is 10-30 ml / min; the ethylene supply is 10-20 ml / min; and the growth temperature is 1100-1300°C.

[0010] The method for preparing high-purity, high-crystallization double-walled carbon nanotubes in large quantities is as follows: before chemical vapor deposition, the tubular reactor is heated to 1100-1300° C. under the protection of nitrogen at a small flow rate of 0.1-0.5 liters / minute.

[0011] The method for preparing high-purity, high-crystallization double-walled carbon nanotubes in large quantities introduces nitrogen into the reaction system to promote catalyst nucleation, adjust the number and size of catalysts, prepare catalysts with uniform particle sizes, and increase the nucleation ratio of double-walled carbon nanotubes in combination with growth kinetics process control.

[0012] The method for preparing high-purity, high-crystallization double-walled carbon nanotubes in large quantities adjusts the ratio of methane, ethylene and toluene, thereby adjusting the carbon source supply rate in the tubular reactor to increase the growth rate and yield of the double-walled carbon nanotubes.

[0013] In the large-scale preparation method of high-purity and high-crystallization double-walled carbon nanotubes, the quantity content of double-walled carbon nanotubes in the prepared carbon nanotube products is higher than 90%.

[0014] The method for preparing a large amount of high-purity and high-crystallization double-walled carbon nanotubes has high crystallinity and an oxidation decomposition temperature range of 700-920°C.

[0015] The method for preparing high-purity and high-crystallization double-walled carbon nanotubes in large quantities has high purity of double-walled carbon nanotubes and a catalyst residue content of less than 6wt%.

[0016] The method for preparing high-purity, high-crystallinity double-walled carbon nanotubes in large quantities has high production capacity and can produce more than 500 cubic centimeters of double-walled carbon nanotube macroscopic bodies per hour in a tubular reactor with a diameter of 6.5 centimeters.

[0017] The design concept of the present invention is:

[0018] The key to the nucleation of double-walled carbon nanotubes is the reasonable matching of the carbon source conversion rate of a single catalyst with the size of the carbon nanotube nucleation site. Catalyst size is one of the main factors affecting the carbon source conversion rate of a single catalyst. In the floating catalyst chemical vapor deposition method, the catalyst precursor diffuses, decomposes, and randomly collides in the carrier gas during the movement from the low temperature zone to the high temperature reaction zone to form catalyst particles. The nucleation of the catalyst is sequential, and the catalyst that nucleates and grows first (relative to the iron atom clusters in the nucleation stage) is more likely to capture free iron atoms and continue to grow, so the catalyst particle size distribution obtained in this process is wide. The carbon source supply is indiscriminate for all catalysts, so only some catalysts match the carbon source to obtain a suitable carbon conversion rate. That is, catalyst particles with suitable sizes or nucleation sites on particles catalyze the growth of double-walled carbon nanotubes, while catalysts or nucleation sites on particles with inappropriate sizes grow carbon products such as carbon nanotubes with other wall numbers or carbon fibers, and the enrichment of double-walled carbon nanotubes is low. Therefore, a catalyst with the right size and uniform particle size is a prerequisite for increasing the probability of double-walled carbon nanotube nucleation. We introduce nitrogen into the reaction system to promote catalyst nucleation and reduce the nucleation time difference, so that the catalysts can nucleate and grow synchronously as much as possible in the same period, so as to obtain a catalyst with the right size and uniform particle size. Combined with the regulation of growth kinetics, it is expected to increase the enrichment of double-walled carbon nanotubes in the product. In the floating catalyst method, materials such as catalysts and carbon sources move synchronously with the carrier gas; the catalyst continuously consumes carbon sources during its movement in the tubular reactor, that is, during the growth of carbon nanotubes, and the growth rate decreases; by optimizing the supply of carbon sources in the tubular reactor, it is expected to increase the growth rate and yield of double-walled carbon nanotubes.

[0019] The advantages and beneficial effects of the present invention are:

[0020] 1. The present invention promotes catalyst nucleation by adding a suitable proportion of nitrogen to the reaction system, adjusts the number and size of the catalyst, and prepares a catalyst with uniform particle size, effectively improving the process weaknesses of the floating catalyst chemical vapor deposition method, such as a single means of catalyst structure control and a wide distribution of catalyst particle size, and combines refined growth kinetics control to prepare a large-scale sample of high-enrichment double-walled carbon nanotubes.

[0021] 2. The product prepared by the present invention has a high enrichment of double-walled carbon nanotubes, with a content greater than 90%; the product is pure, with few impurities, and the catalyst content is less than 6wt%; the carbon nanotubes have high crystallinity, and the oxidation decomposition temperature ranges from 700 to 920°C.

[0022] 3. The preparation process of the present invention is high-yielding, and 500 cubic centimeters of double-walled carbon nanotube macroscopic bodies can be grown per hour in a tubular reactor with an inner diameter of 6.5 centimeters. In addition, the equipment and process are simple, and continuous production can be easily realized. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1.Typical scanning electron microscope photograph of double-walled carbon nanotubes prepared in Example 1.

[0024] Figure 2 .Typical transmission electron microscopy photograph of the catalyst prepared in Example 1.

[0025] Figure 3 . Diameter distribution diagram of catalyst particles prepared in Example 1. In the figure, the horizontal axis dt represents the diameter of the catalyst particles (nm), and the vertical axis Percengtage represents the content percentage (%).

[0026] Figure 4 .Typical high-resolution transmission electron microscopy photograph of double-walled carbon nanotubes prepared in Example 1.

[0027] Figure 5 Laser Raman spectrum of double-walled carbon nanotubes prepared in Example 1, laser wavelength 633 nanometers. In the figure, the horizontal axis Raman Shift (cm -1 ) represents the wave number, and the vertical axis Intensity (au) represents the resonance intensity.

[0028] Figure 6 .Thermogravimetric-differential thermal analysis curve of double-walled carbon nanotubes prepared in Example 1. In the figure, the horizontal axis Temperature represents temperature (°C), the left vertical axis DTA represents the temperature difference between the reference and the sample (μV / mg), and the right vertical axis TG represents the mass percentage (%); Curve 1 is the curve of mass percentage changing with temperature, and Curve 2 is the curve of temperature difference between the reference and the sample changing with temperature.

[0029] Figure 7 .Typical transmission electron microscope photograph of the catalyst prepared in Comparative Example 1.

[0030] Figure 8 . Diameter distribution diagram of catalyst particles prepared in Comparative Example 1. In the figure, the horizontal axis dt represents the catalyst particle diameter (nm), and the vertical axis Percengtage represents the content percentage (%). DETAILED DESCRIPTION

[0031] In the specific implementation process, the present invention adopts a floating catalyst chemical vapor deposition method, dissolves a catalyst precursor and a promoter precursor in toluene to obtain a uniform mixed solution, and uniformly injects it into a high-temperature tubular reactor with a constant flow of carrier gas and a gas carbon source, and grows double-walled carbon nanotubes at 1100-1300°C for 0.5-5 hours.

[0032] Below, the present invention is further described in detail by examples.

[0033] Example 1.

[0034] In this embodiment, a mixed solution of ferrocene, thiophene and toluene with a mass ratio of 15:1.2:100 is first prepared, and ultrasonic treatment is performed at room temperature for 5 minutes for standby use. Under the protection of a small flow rate of 0.3 liters / minute nitrogen, the chemical vapor deposition horizontal tubular reactor (tube diameter 6.5 cm) is heated to 1200°C; then the nitrogen flow rate is adjusted to 5.4 liters / minute, and 3.6 liters / minute of hydrogen, 20 sccm of methane and 10.5 sccm of ethylene are introduced, and at the same time, a mixed solution of ferrocene, thiophene and toluene is uniformly injected at a rate of 15 microliters / minute to grow carbon nanotubes. The growth time is 1 hour, and the product volume is 500 cubic centimeters.

[0035] The products were characterized by scanning electron microscopy: Figure 1 The typical morphology of double-walled carbon nanotube products is shown in Figure 1. The product is very pure and contains very few granular impurities. The catalyst was characterized using transmission electron microscopy: Figure 2 As shown in the figure, the typical morphology of the catalyst shows that the catalyst particle size is uniform. Figure 3 As shown in the figure, the diameters of 100 catalyst particles were measured under a transmission electron microscope and the diameter distribution diagram was drawn. It can be seen that 64% of the catalyst particles have a diameter distribution of 4 to 6 nanometers, 22% of the catalyst particles have a diameter distribution of more than 6 to 8 nanometers, and catalysts of other sizes account for only 14%. Figure 4 As shown, the product was characterized by transmission electron microscopy, and the typical morphology of double-walled carbon nanotubes showed that the product had a high enrichment of double-walled carbon nanotubes. 100 carbon nanotubes were counted under transmission electron microscopy, and the content of carbon nanotubes with different wall numbers was counted; double-walled carbon nanotubes accounted for 91% of the product, single-walled carbon nanotubes accounted for 6%, and triple-walled carbon nanotubes accounted for 3%. Figure 5 As shown, the sample was characterized by laser Raman spectrometer, and the typical Raman spectrum of double-walled carbon nanotube products. It can be seen that the sample has paired RBM peaks in the wave number range of 90 to 170 and 170 to 260, which correspond to the radial vibration of carbon atoms on the outer wall and inner wall of the double-walled carbon nanotube, respectively, indicating that the product is mainly double-walled carbon nanotubes, which is consistent with the characterization results of transmission electron microscopy.

[0036] Thermogravimetric analysis was performed on the samples to evaluate the crystallinity and purity of the macro-samples. Figure 6As shown in the figure, the typical thermogravimetric-differential thermal analysis curve of the prepared double-walled carbon nanotube sample shows that the sample loses very little weight below 650°C, indicating that the content of carbon impurities such as amorphous carbon is very low; in the temperature range of 700-920°C, the sample loses weight quickly, which is the oxidation decomposition process of the double-walled carbon nanotube. The differential thermal analysis curve (DTA) is positive in this range (peak appears at around 800°C), indicating that the sample releases heat in this process, which corresponds to the oxidation heat release of the double-walled carbon nanotube. The thermogravimetric-differential thermal analysis curve shows that the double-walled carbon nanotube sample has strong antioxidant ability, few structural defects, and high crystallinity. According to the thermogravimetric curve, the catalyst content of the double-walled carbon nanotube sample is calculated to be 5.2wt%, proving that the catalyst content of the sample is low, which is consistent with the characterization results of scanning electron microscopy and transmission electron microscopy.

[0037] Example 2.

[0038] In this embodiment, a mixed solution of ferrocene, thiophene and toluene with a mass ratio of 20:1.6:100 is first prepared, and ultrasonic treatment is performed at room temperature for 5 minutes for standby use. Under the protection of nitrogen with a small flow rate of 0.1 liters / minute, the chemical vapor deposition horizontal tubular reactor (tube diameter 6.5 cm) is heated to 1150°C, and then the nitrogen flow rate is adjusted to 6.3 liters / minute, 2.7 liters / minute of hydrogen is introduced, and 14 sccm of methane and 17.5 sccm of ethylene are introduced. At the same time, a mixed solution prepared by ferrocene, thiophene and toluene is uniformly injected at a rate of 15 microliters / minute to grow carbon nanotubes. The growth time is 1 hour, and the product volume is 510 cubic centimeters.

[0039] Scanning electron microscopy characterization shows that the product is very pure and has very few granular impurities. The diameters of 100 catalyst particles were measured under a transmission electron microscope. 62% of the catalyst particles had diameters between 4 and 6 nanometers, 24% of the catalyst particles had diameters greater than 6 to 8 nanometers, and catalysts of other sizes accounted for only 14%. 100 carbon nanotubes were counted under a transmission electron microscope, and the proportion of carbon nanotubes with different wall numbers was counted. Double-walled carbon nanotubes accounted for 90%, single-walled carbon nanotubes accounted for 4%, and triple-walled carbon nanotubes accounted for 6%. The samples were characterized using a laser Raman spectrometer, and it was seen that the samples had paired RBM peaks in the wavenumber ranges of 90 to 170 and 170 to 270, corresponding to the radial vibrations of carbon atoms on the outer and inner walls of double-walled carbon nanotubes, respectively, indicating that the product was mainly double-walled carbon nanotubes, which was consistent with the characterization results of the transmission electron microscope.

[0040] Thermogravimetric analysis was performed on the samples to evaluate the crystallinity and purity of the macro-samples. The oxidative decomposition temperature range of the prepared double-walled carbon nanotube samples was 705-910°C, indicating that the double-walled carbon nanotube samples had strong antioxidant capacity, few structural defects, and high crystallinity. The catalyst content of the double-walled carbon nanotube samples was calculated to be 5.8wt% based on the thermogravimetric curve, proving that the catalyst content of the samples was low, which is consistent with the characterization results of scanning electron microscopy and transmission electron microscopy.

[0041] Example 3.

[0042] In this embodiment, a mixed solution of ferrocene, thiophene and toluene with a mass ratio of 10:0.8:100 is first prepared, and ultrasonic treatment is performed at room temperature for 5 minutes for standby use. Under the protection of a small flow rate of 0.5 liters / minute nitrogen, the chemical vapor deposition horizontal tubular reactor (tube diameter 6.5 cm) is heated to 1300°C, and then the nitrogen flow rate is adjusted to 7 liters / minute, 2 liters / minute of hydrogen is introduced, and 12.5 sccm of methane and 15.5 sccm of ethylene are introduced. At the same time, a mixed solution prepared by ferrocene, thiophene and toluene is uniformly injected at a rate of 20 microliters / minute to grow carbon nanotubes. The growth time is 1 hour, and the product volume is 530 cubic centimeters.

[0043] Scanning electron microscopy shows that the product is very pure and has very few granular impurities. The diameters of 100 catalyst particles were measured under a transmission electron microscope. 60% of the catalyst particles were distributed in the range of 4 to 6 nanometers, 25% of the catalyst particles were distributed in the range of greater than 6 to 8 nanometers, and catalysts of other sizes accounted for only 15%. The content ratio of carbon nanotubes with different wall numbers in 100 carbon nanotubes was counted under a transmission electron microscope. Double-walled carbon nanotubes accounted for 92% of the product, single-walled carbon nanotubes accounted for 2%, and triple-walled carbon nanotubes accounted for 6%. The samples were characterized by a laser Raman spectrometer, and it can be seen that the samples have paired RBM peaks in the wave number range of 80 to 170 and 170 to 260, corresponding to the radial vibration of carbon atoms on the outer wall and inner wall of double-walled carbon nanotubes, respectively, indicating that the product is mainly double-walled carbon nanotubes, which is consistent with the characterization results of transmission electron microscopy.

[0044] Thermogravimetric analysis was performed on the samples to evaluate the crystallinity and purity of the macro-samples. The oxidative decomposition temperature range of the prepared double-walled carbon nanotube samples was 710-915°C, indicating that the double-walled carbon nanotube samples had strong antioxidant capacity, few structural defects, and high crystallinity. The catalyst content of the double-walled carbon nanotube samples was calculated to be 4.8wt% based on the thermogravimetric curve, proving that the catalyst content of the samples was low, which is consistent with the characterization results of scanning electron microscopy and transmission electron microscopy.

[0045] Comparative Example 1.

[0046] In this comparative example, a mixed solution of ferrocene, thiophene and toluene with a mass ratio of 15:1.2:100 was first prepared, and ultrasonic treatment was performed at room temperature for 5 minutes for standby use. Under the protection of a small flow rate of 0.3 liters / minute nitrogen, the chemical vapor deposition horizontal tubular reactor (tube diameter 6.5 cm) was heated to 1200°C, and then the nitrogen was turned off. 9 liters / minute of hydrogen was introduced, and 20 sccm of methane and 10.5 sccm of ethylene were introduced. At the same time, a mixed solution of ferrocene, thiophene and toluene was uniformly injected at a rate of 15 microliters / minute to grow carbon nanotubes. The growth time was 1 hour, and the product volume was 550 cubic centimeters.

[0047] The catalysts were characterized by transmission electron microscopy: Figure 7 As shown in the figure, the typical morphology of the catalyst shows that the catalyst particle size distribution is broad. Figure 8 As shown, the diameter of 100 catalyst particles was measured under a transmission electron microscope, and the diameter distribution diagram was drawn. It can be seen that 23% of the catalyst particles have a diameter distribution of 2-4 nanometers, 26% of the catalyst particles have a diameter distribution of greater than 4-6 nanometers, 14% of the catalyst particles have a diameter distribution of greater than 6-8 nanometers, 17% of the catalyst particles have a diameter distribution of 9-10 nanometers, and 14% of the catalyst particles have a diameter distribution of greater than 10-12 nanometers. Other sizes of catalysts account for 6%. 100 carbon nanotubes were counted under a transmission electron microscope, and the content of carbon nanotubes with different wall numbers was counted; single-walled carbon nanotubes accounted for 88% of the product, double-walled carbon nanotubes accounted for 8%, and triple-walled carbon nanotubes accounted for 4%.

[0048] Comparative Example 2.

[0049] In this comparative example, a mixed solution of ferrocene, thiophene and toluene with a mass ratio of 15:1.2:100 was first prepared, and ultrasonic treatment was performed at room temperature for 5 minutes for standby use. Under the protection of a small flow rate of 0.3 liters / minute nitrogen, the chemical vapor deposition horizontal tubular reactor (tube diameter 6.5 cm) was heated to 1200°C; then the nitrogen flow rate was adjusted to 8.1 liters / minute, and 0.9 liters / minute of hydrogen, 20 sccm of methane and 10.5 sccm of ethylene were introduced, and at the same time, a mixed solution of ferrocene, thiophene and toluene was uniformly injected at a rate of 15 microliters / minute to grow carbon nanotubes. The growth time was 1 hour, and the product volume was 60 cubic centimeters.

[0050] The diameters of 100 catalyst particles were measured under a transmission electron microscope, and it was found that 9% of the catalyst particles were less than 2 nanometers in diameter, 21% of the catalyst particles were 2-4 nanometers in diameter, 18% of the catalyst particles were greater than 4-6 nanometers in diameter, 17% of the catalyst particles were greater than 6-8 nanometers in diameter, 14% of the catalyst particles were 9-10 nanometers in diameter, 16% of the catalyst particles were greater than 10-12 nanometers in diameter, and other sizes of catalysts accounted for 5%. 100 carbon nanotubes were counted under a transmission electron microscope, and the proportion of carbon nanotubes with different wall numbers was counted; double-walled carbon nanotubes accounted for 26% of the product, single-walled carbon nanotubes accounted for 49%, triple-walled carbon nanotubes accounted for 14%, and carbon nanotubes with other wall numbers accounted for 11%.

[0051] The results of the embodiments and comparative examples show that the present invention promotes catalyst nucleation, adjusts the number and size of catalysts, and prepares catalysts with uniform particle size by introducing an appropriate amount of nitrogen into the floating catalyst chemical vapor deposition reaction system, combines refined growth kinetics control to increase the nucleation ratio of double-walled carbon nanotubes, optimizes the carbon source supply rate in the tubular reactor, increases the growth rate of double-walled carbon nanotubes, and then increases the yield, thereby achieving a large-scale preparation of high-purity, high-crystallization double-walled carbon nanotubes. The equipment and process of the present invention are simple, easy to realize continuous production, and are of great significance to promoting the large-scale application of double-walled carbon nanotubes in high-tech fields such as structural functional fibers, composite materials, multifunctional braids, and electronic devices.

Claims

1. A method for preparing high-purity, high-crystallinity double-walled carbon nanotubes in large quantities, characterized in that: The floating catalyst chemical vapor deposition method is adopted, hydrocarbons toluene, methane, and ethylene are used as carbon sources, ferrocene is used as a catalyst precursor, and thiophene is used as a promoter precursor. The specific process flow is as follows: ferrocene and thiophene are dissolved in toluene to form a mixed solution, and the mixed solution is uniformly injected into a tubular reactor, and nitrogen, hydrogen, methane, and ethylene are introduced at the same time to grow double-walled carbon nanotubes; The mass ratio of ferrocene, thiophene and toluene in the mixed solution is (10-25): (0.5-3): 100, the solution injection rate is 10-50 μL / min, the total flow rate of nitrogen and hydrogen is 5-10 L / min, the nitrogen / hydrogen flow ratio is 1.5-4, the methane supply is 10-30 ml / min, the ethylene supply is 10-20 ml / min, and the growth temperature is 1100-1300°C; Before chemical vapor deposition, the tubular reactor is heated to 1100-1300° C. under the protection of nitrogen at a small flow rate of 0.1-0.5 liters / minute.

2. The method for preparing high-purity, high-crystallinity double-walled carbon nanotubes in large quantities according to claim 1, characterized in that: In the prepared carbon nanotube product, the content of double-walled carbon nanotubes is higher than 90%.

3. The method for preparing high-purity, high-crystallinity double-walled carbon nanotubes in large quantities according to claim 1, characterized in that: Double-walled carbon nanotubes have high crystallinity and an oxidative decomposition temperature range of 700 to 920°C.

4. The method for preparing high-purity, high-crystallinity double-walled carbon nanotubes in large quantities according to claim 1, characterized in that: The double-walled carbon nanotubes are of high purity and the catalyst residue is less than 6 wt%.

5. The method for preparing high-purity, high-crystallinity double-walled carbon nanotubes in large quantities according to claim 1, characterized in that: The method has high productivity and can produce more than 500 cubic centimeters of double-walled carbon nanotube macroscopic bodies per hour in a 6.5 cm diameter tubular reactor.

Citation Information

Patent Citations

  • Preparation method of high-conductivity double-walled carbon nanotube film

    CN112279238A

  • Preparation method and application of single / double-walled carbon nanotube

    CN115650210A